Surveying the State of Mental Health: Prevalence, Risk Factors, and Coping Strategies - Dr. Sanjivani S. Sonar, Dr. Amol P. Kharche, Dr. Sandeep H. Patil, Sanket Patil (South Eastern European Journal of Public Health, 2025)
This project explores the mental health of individuals through a survey conducted with 83 participants, aiming to assess various emotional, psychological, and social factors that influence well-being. A total of 47 questions were included in the survey, addressing topics such as stress levels, coping mechanisms, the prevalence of mental health disorders (including anxiety, depression, and burnout), and perceptions of societal stigma surrounding mental health. Participants were also asked about their access to mental health resources, social support systems, and self-care practices. The findings highlight a strong correlation between higher stress levels and the presence of mental health challenges, with significant variations across age, gender, and socioeconomic backgrounds. The survey also emphasizes the role of social support and lifestyle factors in mitigating mental health issues. This study provides valuable insights into the mental health status of the surveyed group and contributes to the broader conversation on mental health awareness, resource accessibility, and the importance of mental health education in various communities. The results call for increased integration of mental health care into public health initiatives and the development of more inclusive mental health resources